The Influence of Soil Parameters on the Impulse and Airblast Overpressure Loading above Surface-Laid and Shallow-Buried Explosives - John Q. Ehrgott Jr.; Stephen A. Akers; Jon E. Windham; Denis D. Rickman; Kent T. Danielson (Shock and Vibration)
The dynamic airblast, fragmentation, and soil ejecta loading environments produced by the detonation of surface-laid and shallow-buried mines are major threats to lightweight military vehicles. During the past several years, the US Army has focused considerable attention on developing improved methods for predicting the below-vehicle environment from these threats for use by vehicle/armor analysts; thereby, improving the survivability of these platforms. The US Army Engineer Research and Development Center recently completed the first year of a three-year effort to experimentally and numerically quantify the blast and fragment loading environments on vehicles due to surface and subsurface mine and IED detonations. As part of this research effort, a series of experiments was conducted to quantify the effects of soil parameters on the aboveground blast environments produced by the detonation of aboveground bottom-surface-tangent, buried top-surface-tangent, and shallow-buried 2.3-kg (5-lb) Composition C4 charges. The experiments were conducted using three different well characterized soils; 10.8% air-filled-voids (AFV) silty sand, 5.4% AFV clay, and 29.8% AFV poorly graded sand. The combined aboveground loads due to airblast and soil debris were measured by an impulse measurement device. The near-surface airblast overpressure was quantified by a series of side-on measurements above the charges at one elevation and three radial distances. This paper summarizes and compares the results of the experimental program with emphasis on defining the effect of soil parameters on the aboveground blast environment.